Development of a Chemistry Learning Model through Integrated STEM Project-Based Learning Using Palm Oil Waste as a Renewable Energy Source - Zulkhairi; Dzikrul Rizki (Postgraduate, University of Mataram, 2026)
This study aimed to develop a chemistry learning model based on Project-Based Learning (PjBL) integrated with STEM, utilizing palm oil waste as a renewable energy context to enhance students’ scientific literacy. The research adopted a research and development approach using the Plomp model. The developed PjBL–STEM model was implemented in senior high school chemistry classes through contextual, project-oriented activities related to palm oil waste utilization. Data were collected using tests, observations, questionnaires, and performance rubrics to examine the quality and impact of the model. The findings indicate that the developed learning model is valid and practical for classroom implementation. Its application resulted in a significant improvement in students’ scientific literacy, particularly in understanding scientific concepts and applying them to real-world sustainability issues. In addition, the learning process supported the development of essential 21st-century skills, including critical thinking, collaboration, creativity, and environmental awareness. Overall, the results demonstrate that the PjBL–STEM learning model based on local renewable energy contexts is effective and feasible for chemistry instruction. The model contributes not only to improving scientific literacy but also to promoting sustainable education aligned with the Sustainable Development Goals (SDGs).